Effect of aerobic exercise training on cGMP levels and blood pressure in treated hypertensive postmenopausal women - Novais, Iane P; Jarrete, Aline P; Puga, Guilherme M; Araujo, Hygor N; Delbin, Maria A; Zanesco, Angelina (Universidade Estadual Paulista, 2017)
Abstract The second messenger cGMP has been largely studied as a therapeutic target in a variety of disorders such as erectile dysfunction, arterial hypertension and heart failure. Evidence has shown thatcGMP activators are less efficient in estrogen-deficiency animals, but no studies exist involving non-pharmacological approacheson NO/cGMP signaling pathway in hypertensive postmenopausal women. The aim of this study is to examine NO/cGMP pathway, redox state and blood pressure in trained treatedhypertensive (HT) postmenopausal women comparing with normotensive (NT) group. The rationale for that is most of HT patients is encouraged by physician to perform exercise associated with pharmacological treatments.Aerobic exercise training (AET) consisted of 24 sessions, 3 times/week.Parameters were evaluated at baseline and after AET for both groups (HT=28; NT=33).In treatedHT group, AET was significantly effective in increasing cGMP concentrations (28%) accompanied by an up-regulation of SOD (97%) and catalase activity (37%). In NT group, we found an increasein SOD activity (58%). TreatedHT postmenopausal women were still responsive to AET increasing cGMP levels and up-regulating antioxidant system. It should also be emphasized that these findings provide information on the circulating biomarkers that might delay the developing of cardiovascular events in this particular population.
Keywords: hypertension; postmenopause; aerobic exercise, cGMP, redox state